2009
DOI: 10.1002/lary.20127
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and antiangiogenesis by fibroblast growth factor 2–targeted Ad‐TK cancer gene therapy

Abstract: These data suggest that FGF2-retargeted Ad-TK produces a combination of expected direct antitumor cytotoxicity and a newly reported antiangiogenesis effect that could prove promising as a novel therapeutic approach in the treatment of FGF receptor-expressing cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
0
14
0
2
Order By: Relevance
“…To overcome these issues, the FGF2-targeted adenoviral system will be the most efficacious when applied to cells that have low CAR and high FGFRs expression. In our previous study, FGFR1 and FGFR2 expression was widely observed in both tumour cells and ECs of the human HNSCC xenograft model (Saito et al , 2009). Several studies have described a two- to 34-fold increase in intratumoral transduction efficiency (Rancourt et al , 1998; Doukas et al , 1999; Qin et al , 2005) and a two-fold increased transduction efficiency of adenoviral TK gene was observed for human HNSCC (Saito et al , 2009).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…To overcome these issues, the FGF2-targeted adenoviral system will be the most efficacious when applied to cells that have low CAR and high FGFRs expression. In our previous study, FGFR1 and FGFR2 expression was widely observed in both tumour cells and ECs of the human HNSCC xenograft model (Saito et al , 2009). Several studies have described a two- to 34-fold increase in intratumoral transduction efficiency (Rancourt et al , 1998; Doukas et al , 1999; Qin et al , 2005) and a two-fold increased transduction efficiency of adenoviral TK gene was observed for human HNSCC (Saito et al , 2009).…”
Section: Discussionmentioning
confidence: 95%
“…The FGF2-targeted system has been shown to induce highly efficient transduction in ECs that express relatively low levels of CAR receptor (Gupta et al , 2006; Saito et al , 2009). It has been reported that angiogenesis is enhanced and the expression levels of FGFR1 and FGFR2 are upregulated in cancer cells and ECs in HNSCC (Dellacono et al , 1997; Riedel et al , 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, sections were incubated with 3,30-diaminobenzidine tetrahydrochloride (DAB)–H 2 O 2 solution for visualisation and were counterstained with haematoxylin. To assess the grade of microvessel growth within the tumour, three views ( × 20) were digitally recorded for each tumour to cover the greatest anti-CD31 staining area for estimation of microvessel development (Mavria et al , 2005; Saito et al , 2009). The relative percentage of CD31-positive area, represented by the microvessel density (MVD) within each high power field, was measured for three separate images with the assistance of ImmunoRatio, an application reviewed in detail by Tuominen et al (2010).…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, both compartments (tumor cells as well as tumor‐associated microvessels) seem to be promising targets in head and neck cancer. In this line, currently, dual targeting antibodies against EGFR and VEGF and fibroblast growth factor‐2‐targeted gene therapy approaches are proposed preclinically with the intent to interfere with both target compartments in HNSCC. Interestingly, VEGF receptor antibodies were shown to overcome resistance to EGFR inhibitors .…”
Section: Introductionmentioning
confidence: 99%